Hydraulic analysis of the water supply system of the Roman city of Perge. (December 2017) - Vekemans, Odile; Haut, Benoit
Abstract: Fluid dynamics is a valuable tool to characterize and to interpret ancient hydraulic remains. In this study, the peculiar water channel situated in the middle of the main street of the ancient Roman city of Perge is investigated. More precisely, the water flow in the channel (and in diversions originating from this channel) is characterized and the results are analyzed in order to gain a better understanding of the city water distribution system. The peculiarity of the system lies in the unusual channel dimensions in Roman standard, as well as in the presence of blocks perpendicular to the flow, regularly placed every 7 m on the whole channel length. Furthermore, upstream of some of the blocks, terracotta pipes are inserted in the walls of the channel. They were bringing water to the east and to the west of the city. The results show that the channel must have been the only north-south water transportation axis of the city and that the presence of the blocks was imperative, not only to ensure the aesthetic of the channel, but also its functionality. Highlights: The peculiar hydraulic system of the Ancient city of Perge is characterized. It is made of a channel with blocs perpendicular to the flow and of lateral pipes. The flowrate in the various parts of the system is evaluated. The presence of blocs is found imperative for the aesthetic and functionality.